Developing 20fit instagram content for increasing brand awareness among competitors - Ariq Saputra, Fadhil; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2018)
Abstract - Indonesia is one of the biggest internet users in Indonesia that is an opportunity for companies to introduce their product into market. Cheaper marketing cost with wider coverage is one of many reasons why companies are starting to leave traditional marketing channel. One of the internet channel is social media. 20FIT is a company that engaged in sports industry. With a concept that people can be fit in only 20 minutes, 20FIT has their own competitive advantage. 20FIT doing their marketing in their Instagram. The problem is not much people know about 20FIT. Gym is still the main choice because the fee is cheaper and the training method is easier. Interview and questionnaire were done then analyzed using SWOT analysis, 5C of Marketing and PEST analysis. The result is he Instagram content of 20FIT is not attractive than Celebrity Fitness as competitor. To find the solution, Steps in Developing Effective Communication from Integrated Marketing Communication were used and the result is 20FIT must create a video content which lack of on their Instagram profile. The video tells a story of an employee who had tough time at work the he or she wants to get freedom from stress and 20FIT is the solution. The video must show positive and negative emotions while the viewer feels the video is relatable to their daily activity so it will viral. The utilization of video content will increase their brand awareness thus will make an alternative choice. Keywords: Social Media, Content, Brand Awareness, Effective Communication, Video Content